2020
DOI: 10.1016/j.npe.2020.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation on the effect of dislocation structures on the retention and distribution of helium ions implanted into silicon

Abstract: To investigate the effect of dislocation structures on the initial formation stage of helium bubbles, molecular dynamics (MD) simulations were used in this study. The retention rate and distribution of helium ions with 2 keV energy implanted into silicon with dislocation structures were studied via MD simulation. Results show that the dislocation structures and their positions in the sample affect the helium ion retention rate. The analysis on the three-dimensional distribution of helium ions show that the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In addition, defects may also be a suitable way to govern the electronic and mechanical performances of 2D-SiGe. In MD simulation, the density of vacancy defects, interstitials defects, and their motion through the lattice can be easily identified by Wigner-Seitz (WS) defect analysis techniques. , In the WS method, to determine the defect density, two types of configurations are used. One is reference configuration (defect-free structure), and another is displaced configuration (vacancy-induced system).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, defects may also be a suitable way to govern the electronic and mechanical performances of 2D-SiGe. In MD simulation, the density of vacancy defects, interstitials defects, and their motion through the lattice can be easily identified by Wigner-Seitz (WS) defect analysis techniques. , In the WS method, to determine the defect density, two types of configurations are used. One is reference configuration (defect-free structure), and another is displaced configuration (vacancy-induced system).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the displacement peak formed under 0.5 MeV irradiation, the time of the displacement peak The thickness of the constant-temperature walls was set to 2a, and the Langevin thermostat was used to maintain a constant temperature of 300 K for the atoms inside the walls so that excess kinetic energy introduced by PKA could be dissipated by the walls [47]. A fixed layer with a thickness of about 3a was selected as the bottom layer of the system to prevent the entire simulation system from drifting during the collision cascade process [18,21]. The remaining atoms were in the active region, and all atoms in the active region were restricted to adiabatic motion using the NVE ensemble [44,45].…”
Section: Simulation Of Radiation Damage In Gan By Single α-Particle I...mentioning
confidence: 99%
“…The results showed that as the temperature increased from 300 K to 350 K, the atomic loss in GaN increased, and the atomic mechanical stability decreased. Li [ 21 ] used molecular dynamics simulations to study the injection of α-particles into single-crystal silicon, and the results showed that a dislocation structure was produced during the injection process. Fan et al [ 22 ] used Monte Carlo calculations to simulate the irradiation of aluminum materials by protons and α-particles.…”
Section: Introductionmentioning
confidence: 99%